Educational Intervention Proposal for the Basic Health Team on Physical Activity in Pregnant Women - Ismaray Sacerio González; Lourdes Elena Duany Badell; Isabel Cristina Jiménez Ramos; Isaac Rodríguez Palacios; Lázaro Armando Águila Trujillo; Yolaine Basulto Vázquez (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: physical activity has been identified as one of the main factors for global mortality and is increasing in many countries. Objective: to develop a proposal for an educational intervention strategy for the Basic Health Team on physical activity during pregnancy. Methods: a type of research was carried out: Research, development and innovation in which a descriptive design is assumed. The universe consisted of 72 professionals. The database and the processing of these was done using SPSS, Version 25.0. Absolute numbers and percentage were used for descriptive statistics and standard deviation for variable variability. For quantitative variables, the arithmetic mean and standard deviation. The validation of knowledge instruments was carried out using the Moriyama method. Results: 44.5 % of the professionals were found in the age group of 25 to 29 years, females represented 89.0 %. Licensed nurses represented 36.1 % and with more than 10 years of graduation representing 45.8 %. 90.3 % do not have a history of previous training. Only 26.3 % of the core team members answered the questionnaires correctly. Conclusions: the Basic Health Team is mostly made up of women with work experience of more than 10 years, but without previous training. There were gaps in knowledge, hence the importance of carrying out educational and awareness interventions to raise the level of knowledge, incorporate pregnant women to practice physical activity and improve their quality of life.